The Hybrid warfare of America against Islamic Republic of Iran - Fathollah Kalantari (علوم و فنون نظامی)
A combined war, which is referred to as a complex operation, includes targeted and planned actions by a governmental or non-governmental actor against the components of a country's national power in order to overthrow or disable the target country. Nationality depends on the strategy, methods, tools, power of the attacking force and the purpose of the combined war. The main purpose of this article is to explain the nature, principles, and characteristics of America's combined war against Iran. This article is applied and done by analytical-explanatory method. The collection tool was library and field, the sample size is 45 people. According to the findings of the research, the combined war of America against Iran is a combination of hard, soft and smart power based on the combination of "collapse from inside and pressure from outside" strategy. Based on this strategy, he always announced that all options are on the table to deal with Iran. According to the results of the research, the combined war of America against Iran is based on the combination of strategies, methods and tools, and this war has 10 principles and 24 characteristics.